2018
DOI: 10.7554/elife.33420
|View full text |Cite
|
Sign up to set email alerts
|

Role of the visual experience-dependent nascent proteome in neuronal plasticity

Abstract: Experience-dependent synaptic plasticity refines brain circuits during development. To identify novel protein synthesis-dependent mechanisms contributing to experience-dependent plasticity, we conducted a quantitative proteomic screen of the nascent proteome in response to visual experience in Xenopus optic tectum using bio-orthogonal metabolic labeling (BONCAT). We identified 83 differentially synthesized candidate plasticity proteins (CPPs). The CPPs form strongly interconnected networks and are annotated to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 90 publications
2
33
0
Order By: Relevance
“…Here, Liu et al identified over 5000 newly synthesized proteins overall and 80 candidate plasticity proteins that were differentially translated following visual cues [47]. Many of these novel candidate proteins have mammalian homologs and are reportedly implicated in neurodegenerative diseases [47]. By extensively characterizing and validating these results, these reports confirm the integral role of protein synthesis in experience-dependent plasticity in Xenopus and suggest similar mechanisms in mammals.…”
Section: Metabolic Labeling Of Nascent Peptidesmentioning
confidence: 61%
See 2 more Smart Citations
“…Here, Liu et al identified over 5000 newly synthesized proteins overall and 80 candidate plasticity proteins that were differentially translated following visual cues [47]. Many of these novel candidate proteins have mammalian homologs and are reportedly implicated in neurodegenerative diseases [47]. By extensively characterizing and validating these results, these reports confirm the integral role of protein synthesis in experience-dependent plasticity in Xenopus and suggest similar mechanisms in mammals.…”
Section: Metabolic Labeling Of Nascent Peptidesmentioning
confidence: 61%
“…Remarkably, their BONCAT experiments identified a single protein, cytoplasmic polyadenylation element binding protein (CPEB), whose acute synthesis following visual-conditioning regulated the link between translation and behavioral plasticity [46]. The Cline group went on to further utilize BONCAT to assess the nascent proteome following visual cues in Xenopus tadpoles, employing a shorter, five-hour incubation with AHA [47]. Here, Liu et al identified over 5000 newly synthesized proteins overall and 80 candidate plasticity proteins that were differentially translated following visual cues [47].…”
Section: Metabolic Labeling Of Nascent Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Proximity-based biotin tagging has been invaluable for studying subcellular and molecular phenomena, such as proteomic characterization of organelles or synaptic cleft proteins in reduced experimental systems (Loh et al, 2016; Rhee et al, 2013). Similarly, strategies to label newly synthesized proteins demonstrated proteomic dynamics in response to plasticity paradigms and axon guidance cues (Alvarez-Castelao et al, 2017; Cagnetta et al, 2018; Liu et al, 2018; Schanzenbächer et al, 2016). In vivo NHS-biotin labeling increases coverage of protein biotinylation, partly by removing the dependence on new protein synthesis, and thereby allows the unbiased study of protein transport.…”
Section: Discussionmentioning
confidence: 99%
“…These approaches, called bio-orthogonal noncanonical amino acid tagging (BONCAT; Dieterich et al, 2006) and fluorescent noncanonical amino acid tagging (FUNCAT; Dieterich et al, 2010) respectively, have been used to measure changes in protein synthesis in response to neurotrophic factors (Dieterich et al, 2010;Genheden et al, 2015;Bowling et al, 2016), dopaminergic transmission (Hodas et al, 2012), activity-dependent homeostatic plasticity (Schanzenbächer et al, 2016(Schanzenbächer et al, , 2018, as well as the induction of long-term synaptic depression (Younts et al, 2016;van Gelder et al, 2020). BONCAT/FUNCAT have also been used to label whole organisms and demonstrate neural activity-dependent changes in protein translation during larval zebrafish (Hinz et al, 2012) and frog development (Shen et al, 2014;Liu and Cline, 2016;Liu et al, 2018).…”
Section: Investigating Nascent Protein Synthesis In Subcellular Compamentioning
confidence: 99%